the wahhabi movement in representations of orientalist travel (construction of image) - writings of Jhon lewis Burckhardt as model - - yazir, djamel (The Algerian Historical Journal, 2026)
This research paper aims to identify the location of the Wahhabi movement and its first state Saudi Arabia at the beginnig of the nineteenth century, in the writings of the English Orientalist traveler " Jhon lewis Burckhardt" and what it contains of scientific and academic knowledge can be counted as an objective source container trusted within the scope of the studies and researchs on this subject, where "Burckhardt" conveyed to us a gorup of realistic perceptions that he witnessed and lived with its events and details, in the form of the Orientalist travel literature imagination and including his writings on the Orient in general, his Oriental travels has yielded a group of the literatures that lists and decomposes the reality of conflict between the first Saudi Arabia state and ottman empire by mohamed Ali Bacha, also the nature of systems and the effects of its existence on reality of Al hijaz during that period .